Optimum blue light proportions enhance growth and phytochemicals in Ivy-Gourd (Coccinia grandis L. Voigt) microgreens - W. Gnanathilaka, K G Sachini; Wattanachaiyingchareon, Det; Wattanachaiyingchareon, Wandee; Thongket, Thammasak (Agriculture and Natural Resources, 2025)
Importance of the work: Ivy-gourd is a nutrient-rich but underutilized microgreen. Light spectrum, especially blue and red light ratios, influences plant growth and phytochemicals. This study explored optimal light combinations to enhance growth and quality in ivy-gourd microgreens. Objectives: To produce ivy-gourd microgreens in a plant factory under different ratios of blue (B) and red (R) light combinations and to investigate its growth and phytochemical properties. Materials and Methods: A 3 ×6 factorial in a randomized complete block design was used. Factor A was three ivy-gourd accessions from Thailand and factor B was six different light combinations using white (W), monochromatic red (R) and monochromatic blue (B) and three combinations of varying B-to-R ratios (B75:R25, B50:R50, B25:R75). Results: There were significant differences in growth and carotenoid content among the accessions (p < 0.05), while there was no significant difference in the phytochemical content. However, all parameters were significantly different under the B and R light combinations. Monochromatic R light promoted the growth and demoted the phytochemicals. Contrarily, increasing the B light percentage caused decreased growth and increased phytochemical levels. The non-linear regression analysis revealed a strong correlation (coefficient of determination > 0.8) between increasing the B light amount and each of fresh weight, hypocotyl length, vitamin C, 2,2-diphenyl-1- picrylhydrazyl (DPPH) antioxidant activity, phenolic compounds and total soluble solids, while pigments and dry weight did not show such a correlation. Main finding: There was a specific optimum level of the B light ratio to maximize each phytochemical. The growth parameters were maximized under monochromatic R light. In contrast, phenolic compounds and the DPPH antioxidants peaked close to 100% B light, while the total soluble solids and vitamin C content maximized in the range 50−75% B light.